Divergent Serpentoviruses in Free-Ranging Invasive Pythons and Native Colubrids in Southern Florida, United States - Steven B. Tillis; Jillian M. Josimovich; Melissa A. Miller; Laura L. Hoon-Hanks; Arik M. Hartmann; Natalie M. Claunch; Marley E. Iredale; Tracey D. Logan; Amy A. Yackel Adams; Ian A. Bartoszek; John S. Humphrey; Bryan M. Kluever; et al. (Viruses, 2022)
Burmese python (Python bivittatus) is an invasive snake that has significantly affected ecosystems in southern Florida, United States. Aside from direct predation and competition, invasive species can also introduce nonnative pathogens that can adversely affect native species. The subfamily Serpentovirinae (order Nidovirales) is composed of positive-sense RNA viruses primarily found in reptiles. Some serpentoviruses, such as shingleback nidovirus, are associated with mortalities in wild populations, while others, including ball python nidovirus and green tree python nidovirus can be a major cause of disease and mortality in captive animals. To determine if serpentoviruses were present in invasive Burmese pythons in southern Florida, oral swabs were collected from both free-ranging and long-term captive snakes. Swabs were screened for the presence of serpentovirus by reverse transcription PCR and sequenced. A total serpentovirus prevalence of 27.8% was detected in 318 python samples. Of the initial swabs from 172 free-ranging pythons, 42 (24.4%) were positive for multiple divergent viral sequences comprising four clades across the sampling range. Both sex and snout-vent length were statistically significant factors in virus prevalence, with larger male snakes having the highest prevalence. Sampling location was statistically significant in circulating virus sequence. Mild clinical signs and lesions consistent with serpentovirus infection were observed in a subset of sampled pythons. Testing of native snakes (n = 219, 18 species) in part of the python range found no evidence of python virus spillover; however, five individual native snakes (2.3%) representing three species were PCR positive for unique, divergent serpentoviruses. Calculated pairwise uncorrected distance analysis indicated the newly discovered virus sequences likely represent three novel genera in the subfamily Serpentovirinae. This study is the first to characterize serpentovirus in wild free-ranging pythons or in any free-ranging North America reptile. Though the risk these viruses pose to the invasive and native species is unknown, the potential for spillover to native herpetofauna warrants further investigation.